Experiences and social impact in the application of requirements engineering in the development of an intelligent platform - Maquera, Gladys (2019)
Rural community tourism (RCT) is an activity that contributes, from rural areas, to the socioeconomic and sustainable development of a country. The purpose of this research study was to develop an Intelligent Platform (IP) that meets the needs of the different stakeholders of the RCT. It presents the experience focused on requirements engineering, going through different iterations, where the SWOT analysis was performed, along with the use of extreme programming, compliance with ISO 25010, among others. The precise identification of the requirements was crucial for the implementation and usability of the platform to have a social impact on the direct actors.